JNK signaling coordinates epithelial cell turnover through exocytosis in Drosophila ribosomal protein mutants - Nanami Akai; Yoshimasa Yagi; Tatsushi Igaki; Shizue Ohsawa (iScience)
Summary: Robust tissue growth is orchestrated by the precise coordination of cell death and cell proliferation. In the developing wing pouches of Drosophila Minute/+ animals, both cell death and compensatory cell proliferation are increased, thereby contributing to robust growth of mutant tissue. Here, we show that JNK-mediated elevation of exocytosis in dying cells is crucial for triggering cell turnover in M/+ wing morphogenesis. Mechanistically, elevated JNK signaling in dying cells upregulates exocytosis-related genes and Wingless (Wg), leading to enhanced Wg secretion. Notably, increased exocytosis promotes caspase activation via an exocytosis-Dronc amplification loop, sustaining apoptotic signaling while reinforcing Wg secretion through Dronc activation. Furthermore, this exocytosis-mediated Wg secretion and apoptotic feedback loop universally occurs downstream of JNK signaling, regardless of the genetic background. Overall, our findings provide mechanistic insights into robust tissue growth through the orchestration of cell turnover, primarily via JNK-mediated exocytosis during Drosophila Minute/+ wing morphogenesis.